The Computerized Database of Labrador Inuttut: A Language Revitalization Technology Component - Smith, Lawrence (Études Inuit Studies, 2024)
We present empirical results from the coupling of traditional linguistic research with computational technology, validating a hypothesis that this combination provides benefits beyond either alone. An experiential software innovation now offers automatic and clear visual diagrams of native language structures in full sentence contexts for a quick experiential understanding of how the language fundamentally operates. Such advances for cultural learning and maintenance are now possible because native linguistic polysynthetic structure is systematically integrated in computational technologies. Results from the Computerized Database of Labrador Inuttut are ongoing. Threatened languages can thus be renewed by technology even when they have been diminished by the inexorable domination of superstrate forces in culture and media. We propose continued computational linguistic resource development to enable language and cultural sustenance via new experiential technologies based on both inherent linguistic structure and computational processing.